2008
DOI: 10.1242/dev.029678
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Disp1 is required in sonic hedgehog-expressing cells for paracrine activity of the cholesterol-modified ligand

Abstract: There was a reanalysis of data required to support the findings in Development 132, 133-142.We have repeated the facial analysis reported in Fig. 2 to provide the data required to support some of the original findings of this study (see Publisher's note). Our findings substantiate the original conclusions drawn from Fig. 2 of a dose-related genetic interaction between Disp1 and Shh alleles, and of the function of Disp1 within Shh-producing cells. Some differences are reported below, which might reflect slight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 2 publications
3
41
0
Order By: Relevance
“…Pax7 is a class II factor that is repressed by Shh and is expressed in all dorsal progenitor domains, whereas Nkx6.1 (Nkx6-1 -Mouse Genome Informatics) is a class I factor that is induced by Shh and expressed in the broad ventral progenitor domains of V2 (p2) mutants, all ventral cell types were generated at defined locations (Fig. 6), in agreement with previously reported ShhN function in the spinal cord (Tian et al, 2005). The number of floorplate cells labeled by Foxa2 was comparable between control and Shh N/-embryos (Fig.…”
Section: Widespread Activation Of Ventralsupporting
confidence: 89%
See 2 more Smart Citations
“…Pax7 is a class II factor that is repressed by Shh and is expressed in all dorsal progenitor domains, whereas Nkx6.1 (Nkx6-1 -Mouse Genome Informatics) is a class I factor that is induced by Shh and expressed in the broad ventral progenitor domains of V2 (p2) mutants, all ventral cell types were generated at defined locations (Fig. 6), in agreement with previously reported ShhN function in the spinal cord (Tian et al, 2005). The number of floorplate cells labeled by Foxa2 was comparable between control and Shh N/-embryos (Fig.…”
Section: Widespread Activation Of Ventralsupporting
confidence: 89%
“…Accordingly, it has been proposed that cholesterol modification is required for the formation of Shh multimers involved in long-range signaling and proper vertebrate forebrain patterning (Feng et al, 2004). However, a more recent study suggested that ShhN retained some paracrine activity because it was capable of inducing several ventral neuronal cell types in the spinal cord (Tian et al, 2005). Given this controversy, the role of the cholesterol moiety in Shh function has been re-assessed recently in the limb bud (Li et al, 2006).…”
Section: Region-specific Requirement For Cholesterol Modification Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, ShhN, which lacks the cholesterol moiety, would be expected to spread more rapidly and to penetrate further into the tissue. Surprisingly then, ventral neural tube patterning is compacted in mice that express ShhN in place of wild-type Shh (Huang et al, 2007;Tian et al, 2005). This might reflect a decreased range for ShhN as compared with fully processed ShhNp and/or a reduced activity of the monomeric form.…”
Section: Shh Lipidation Affects Its Production and Spreadmentioning
confidence: 99%
“…How Disp1 promotes the release of ShhNp remains to be determined, but its requirement is limited to lipidated Shh; Shh lacking cholesterol (ShhN) undergoes Disp1-independent secretion ( Fig. 3) (Tian et al, 2005). One possible action of Disp1 is to facilitate the assembly of soluble ShhNp multimers that are long-range, high-activity signaling complexes (Goetz et al, 2006;Zeng et al, 2001).…”
Section: Shh Lipidation Affects Its Production and Spreadmentioning
confidence: 99%